Conus Medullaris Metastatic Tumours - De, Subir; Jain, Atul; Gupta, Vijay Kumar; Carvalho, Ajay Sebastian; Patel, Love M (Nepal Journal of Neuroscience, 2025)
Intramedullary spinal cord metastatic tumors are rare clinical entity, with primary tumors like ependymomas and astrocytomas being most common. With the improved survival due to early detection and advanced therapeutic management of cancer patients, incidence of intramedullary spinal cord metastasis (IMSCM) is increasing. Conus metastasis is very uncommon among intramedullary spinal cord metastasis in published literature. We present a short series of two cases of conus medullaris (CM) metastasis from primary lung cancer treated surgically at our institution and discuss the surgical outcome and review of literature.